Block by Phytoestrogens of Recombinant Human Neuronal Nicotinic Receptors - Ken Nakazawa; Yasuo Ohno (Elsevier, 2003)
ABSTRACT: The effects of phytoestrogens on neuronal nicotinic acetylcholine receptor/channels were examined by expressing recombinant channels in Xenopus oocytes. When functional channels were expressed with human α4 and β2 subuints, daidzein (10 and 100 μM) partially inhibited the ionic current activated by acetylcholine. The current inhibition was also observed when functional channels were expressed with human α3 and β4 subunits or rat homologues. Genistin (100 μM) also inhibited the acetylcholine-activated current. Tamoxifen (100 μM), an antiestrogen did not antagonize the inhibition by daidzein. The results suggest that phytoestrogens, like estrogens and xenoestrogens, block human neuronal acetylcholine receptors through non-genomic mechanisms.